Auditory Stimuli in Neuro-marketing Practices; Case: Unicentro Shopping Mall in Cúcuta, Colombia - Avendaño Castro, William R.; Paz Montes, Luisa S.; Rueda Vera, Gerson (Cuadernos de Administración, 2015)
The current market competitive setting involves the strategic application of neuro-marketing as an aid to increase consumerism and prevalence of brands and products. Sensory stimulation is used as a valuable technique within the business context, that is, sensory marketing. This research sought to evaluate auditory marketing practices through sound stimuli in 52 commercial establishments in the Unicentro shopping mall, one of the most outstanding in the city of Cúcuta, Norte de Santander, Colombia. The sample size comprised 30 establishments dedicated to textiles, 15 to foods, 2 to entertainment, 2 to books, and 3 to technology. The information was gathered through the application an auditory sensory uptake matrix, highlighting the sound characteristics of the shopping center and the establishments, besides reactions from visitors to sound stimuli and their location. The results evidence inadequate use of auditory marketing by a representative number of establishments and its absence in others, which reflects the need to implement effective auditory strategies that permit attracting clients and, hence, induction of purchases through their permanence in the commercial spaces